PROJECT BASED LEARNING ACTIVITIES : MEDIA POWTOON DALAM PEMBELAJARAN IPA SD UNTUK MENGANALISIS KETERAMPILAN BERFIKIR KREATIF MAHASISWA - Imelda Free Unita Manurung (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
ABSTRACT This study aims to determine the creative thinking skills possessed by students through project based learning activities in the form of making media powtoon. This research is a descriptive study to see how far students are able to think creatively to produce a product in learning science in elementary school. The analysis results obtained based on the percentage results show that the creative thinking skills possessed by students are quite good when viewed from the products produced. The percentage value of creative thinking skills from project learning activities obtained included group 1 by 27%, group 2 by 25%, group 3 by 30%, and group 4 by 18%.Keywords: Project Based Learning Activities, Powtoon ABSTRAK Penelitian ini bertujuan untuk mengetahui keterampilan berfikir kreatif yang dimiliki oleh mahasiswa melalui project based learning activities berupa pembuatan media powtoon. Penelitian ini merupakan penelitian deskriptif untuk melihat sejauhmana mahasiswa mampu berfikir kreatif untuk menghasilkan sebuah produk dalam pembelajaran IPA di SD. Hasil analisis yang diperoleh berdasarkan hasil presentase menunjukan bahwa keterampilan berfikir kreatif yang dimiliki oleh mahasiswa sudah cukup baik jika dilihat dari produk yang dihasilkan.  Nilai presentase keterampilan berfikir kreatif dari aktivitas pembelajaran proyek yang diperoleh antara lain kelompok 1 sebesar  27%, kelompok 2 sebesar 25%, kelompok 3 sebesar 30%, dan kelompok 4 sebesar 18%. Kata Kunci : Project Based Learning Activities, Powtoon